Konflik Batin Tokoh Utama dalam Novel Perempuan Di Titik Nol Karya El-Saadewi - Enny Muliandayani, Ni Kadek; Sudewa, I Ketut; Nama, I Ketut (Humanis, 2016)
This thesis entitled "The Inner Conflict Main Figures in the Novel Women at Work Zero Point El-Saadewi". Novel Woman at Zero Point has a strong psychological picture of the main character. The problems discussed there are two, namely: analysis of the structure and inner conflict. The purpose of this study to determine the structure and the inner conflict of the main character. The methods and techniques used in the study, there are three, namely: (1) methods and techniques of data collection, used qualitative methods and techniques read, see, and note; (2) Methods and techniques of data analysis used descriptive analytic method followed by techniques see, and note; (3) Methods and techniques of presentation of the results of data analysis using the description and presentation of the results of data analysis techniques presented in the format of preparation of the thesis. Structural elements are analyzed in a novel Women in Ground Zero, namely: characterization, plot, and setting. The third analysis used functional structure, because the elements support each other to establish the integrity of the story. Inner conflict such as physical violence and sexual abuse from childhood to adulthood. Solutions done to resolve inner conflict, namely: sublimation, projection, and rationalization.